STRATEGIES FOR TEACHING WRITING SKILLS TO YOUNG LANGUAGE LEARNERS - Baymakova Sarvinoz Abdulaziz qizi (TADQIQOTLAR, 2026)
Abstract: Learning to write in a new language is an essential skill, especially for young learners who are just beginning their educational journey. Writing not only involves putting words on paper but also includes a range of cognitive and creative skills, including vocabulary use, sentence structure, grammar, coherence, and, significantly, motivation and confidence. Effective writing instruction can have a major impact on a child’s academic development and communication abilities.